Analysis of global trends in the european venture capital market - Vyhivska , Iryna; Khomenko , Hanna (Public Policy and Accounting, 2022)
The article examines the relationship between the innovative development of the country's economy, the amount of venture funding for innovation projects, investment freedom and the tax system in the country using an empirical study of their causality and the impact of these factors on each other. The correlation is set at 0,59. An assessment of each of the factors on the level of innovative development of the country was made. Indicators for 16 European countries were taken for analysis. The most stable relationship is found between the country's innovative development and investment freedom. The correlation between innovative development and the volume of venture financing of innovative enterprises, as well as between innovations and features of tax policy in the country is somewhat smaller, but still significant. It is established that the availability of venture capital and the development of venture capital in a country will have a tax policy (special taxation, reduction of capital gains tax). It is established that the development of venture business in the country is important because it provides commitment to the innovation sector of long-term financial resources of institutional and individual investors.